Optimalisasi Pengelolaan Perpustakaan Sekolah melalui Perawatan Koleksi, Desain Tata Ruang, dan Implementasi SLiMS di SMPN 4 Pujon Satu Atap - Alisia Dwi Lutviana; Teguh Darma Pinandhita; Nisa’ Nur Rochma; Muhammad Izzun Ni’am; Fitratul Uyun (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IAIN Lhokseumawe, 2025)
School libraries play a crucial role in strengthening literacy culture; however, many educational institutions at the primary and secondary levels continue to face challenges related to collection management, limited physical space, and the low utilization of technology. This community service program aims to optimize the library management at SMPN 4 Pujon Satu Atap through a technology-based and spatial revitalization strategy. The method employed is the Asset-Based Community Development (ABCD) approach, consisting of five key stages: Discovery, Dream, Design, Define, and Destiny. The activities included identifying library assets and problems, redesigning the reading space, maintaining collections, and implementing digitalization using the SLiMS system. The results indicate a significant improvement in the effectiveness of library management, including faster book circulation processes, enhanced information access, and an increase in student visits by up to 30% within six months. The redesigned library layout also created a more comfortable learning environment and encouraged greater student engagement in literacy activities. SLiMS-based digitalization improved the accuracy of collection records and reduced delays in book returns. The study concludes that a technology-supported ABCD-based revitalization model can enhance the quality of school library services and can be replicated in other schools facing similar challenges.